Different services resource scheduling in LTE - Kadatskaja, О. I.; Nkaru Chizoba Kingsley; Kingsley, S. А. (ХНУРЕ, 2021)
Data transmission networks face extreme challenges in providing high data rate and low latency. In this paper identify main challenges of the art uplink/downlink cheduling in LTE, scheduling GBR and non-GBR services.
Keywords: Different services; Resource sheduling